In Vitro Enzyme Assays for JmjC‐Domain‐Containing Lysine Histone Demethylases (JmjC‐KDMs). Issue 1 (2nd April 2018) - Tarhonskaya, Hanna; Tumber, Anthony; Kawamura, Akane; Schofield, Christopher J.
Abstract: Histone modifications, including lysine methylation marks on histone tails, modulate the accessibility of genes for transcription. Changes in histone tail methylation patterns can cause transcriptional activation or repression. The dynamic regulation of lysine methylation patterns is enabled by two distinct groups of enzymes: histone methyltransferases (KMTs) and demethylases (KDMs). The Jumonji C (JmjC) domain–containing lysine histone demethylases (JmjC‐KDMs) alter the methylation levels of histone tails by removing tri‐, di‐, or mono‐methylation marks. Because JmjC‐KDMs activities are dysfunctional in cancer and other clinical conditions, they are targets for drug discovery. Efforts are underway to develop high‐throughput assays capable of identifying selective, small‐molecule inhibitors of KDMs. Detailed in this unit are protocols for mass spectrometry–based and formaldehyde dehydrogenase–coupled enzyme‐based assays that can be used to identify inhibitors of JmjC‐KDMs. © 2018 by John Wiley & Sons, Inc.